Fluoro-Aryl Substituted α,β2,3-Peptides in the Development of Foldameric Antiparallel β-Sheets: A Conformational Study - Bucci, Raffaella; Contini, Alessandro; Clerici, Francesca; Beccalli, Egle Maria; Formaggio, Fernando; Maffucci, Irene; Pellegrino, Sara; Gelmi, Maria Luisa (Frontiers in Chemistry, 2019)
α,β-Disteroisomeric foldamers of general formula Boc(S-Ala-β2,3D)nOMe were prepared from syn-β2,3-diarylamino acids and S-alanine. Our peptides show two appealing features for biomedical applications: the presence of fluorine, attractive for non-covalent interactions, and aryl groups, crucial for π-stacking. A conformational study was performed, using IR, NMR and computational studies of tetra- and hexapeptides containing the above amino acid in both the R,R-β2,3- and S,S-β2,3-stereochemistries. We found that the stability of peptide conformation is dependent from the stereochemistry of the β-amino acid. Combining S-Ala with R,R-β2,3-diarylamino acid, a stable extended β-strand conformation was obtained. Furthermore, R,R-β2,3-hexapeptide self-assembles to form antiparallel β-sheet structure stabilized by intermolecular H-bonds and π,π-interactions. These features make peptides containing the R,R-β2,3-fluoro amino acid very appealing for the development of bioactive proteolytically stable foldameric β-sheets as modulators of protein-protein interaction (PPI).